2019
DOI: 10.1002/jclp.22767
|View full text |Cite
|
Sign up to set email alerts
|

Bicultural stress, coping, and psychological functioning among Mexican‐descent and White college students

Abstract: Objective The present study investigates associations between bicultural stress, coping, and responses to stress (RTS) in relation to depressive symptoms and self‐esteem for Mexican‐descent and non‐Latinx White college students. Method With a sample of 268 Mexican‐descent and non‐Latinx White college students, two multiple‐mediation path models and two moderation models are examined. Results The hypothesized mediation models were both supported indicating higher bicultural stress is associated with higher repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Indeed, several studies have documented the detrimental impact of ethnic/ racial discrimination across a number of indicators of adjustment (e.g., Castro et al, 2022;Cheng & Mallinckrodt, 2015). Similarly, numerous studies have indicated positive relations between bicultural stressors/stress 1 with depressive symptoms (e.g., Piña-Watson et al, 2019) and positive functioning (e.g., Meca, Webb, et al, 2022;Piña-Watson et al, 2019). Collectively, cultural stressors have been shown to be associated with lower well-being (e.g., Schwartz et al, 2022) and greater internalizing problems (e.g., Polanco-Roman & Miranda, 2013).…”
Section: Conceptualization Of Cultural Stressmentioning
confidence: 99%
“…Indeed, several studies have documented the detrimental impact of ethnic/ racial discrimination across a number of indicators of adjustment (e.g., Castro et al, 2022;Cheng & Mallinckrodt, 2015). Similarly, numerous studies have indicated positive relations between bicultural stressors/stress 1 with depressive symptoms (e.g., Piña-Watson et al, 2019) and positive functioning (e.g., Meca, Webb, et al, 2022;Piña-Watson et al, 2019). Collectively, cultural stressors have been shown to be associated with lower well-being (e.g., Schwartz et al, 2022) and greater internalizing problems (e.g., Polanco-Roman & Miranda, 2013).…”
Section: Conceptualization Of Cultural Stressmentioning
confidence: 99%